An integrated finite particle method with perfectly matched layer for modeling wave-structure interaction. Issue 1 (2nd January 2019) - Weng, X.; Huang, C.; Long, T.; Li, S. M.; Liu, M. B.
ABSTRACT: Numerical simulation of wave-structure interaction is an important but challenging topic due to the movement, deformation and even breakup of free surface, and strong fluid-structure interaction. The implementation of far-field boundary condition is crucial for numerical simulations of wave-structure interaction to avoid the disturbance of reflected waves. In this paper, an integrated finite particle method (FPM) with perfectly matched layer (PML) is developed for modeling wave-structure interaction problems. The PML uses a fictitious layer based on the concept of physical damping to control the wave reflection in a wave tank. The FPM with PML is first used to model the regular wave propagation and it is found that the obtained numerical results are in good agreement with analytical solutions or existing reference results. It is further proved that PML with a properly selected length of wave tank can effectively remove the traveling waves and reproduce the far-field effects. The FPM with PML is then used to model the oscillating wave surge converter (OWSC). The results show that the time-averaged power of OWSC strongly depends on the PTO damping coefficients, the wave periods and the distance between the OWSCs.